Graphene Oxide as a Biocompatible and Osteoinductive Agent to Promote Implant Osseointegration in a Rabbit Tibia Model. Issue 28 (4th September 2022) - Kwak, Jeong Min; Kim, Jungho; Lee, Chung‐Sung; Park, Il‐Soo; Lee, Min; Min, Dal‐Hee; Yeo, In‐Sung Luke
Abstract: Graphene, a nanomaterial made of sp 2 hybridized carbon atoms, has recently been investigated as a novel surface treatment for promoting osseointegration. This study aims to evaluate the biological effects of graphene oxide (GO) on turned and sandblasted, large‐grit, and acid‐etched (SLA) titanium surfaces. In vitro, bone marrow stromal cells (BMSCs) and human gingival fibroblasts (HGFs) are seeded onto titanium discs, whose surfaces have been treated in four different ways (SLA and/or GO), to observe its effects on cellular responses such as adhesion, proliferation and differentiation. In vivo, a rabbit tibia model is used to observe the effects of the four surface treatments on osseointegration of screw‐shaped titanium implants. The bone‐to‐implant contact is analyzed using light microscopic histomorphometry. GO significantly promotes the viability, proliferation and osteoblast differentiation of BMSCs, and it enhances the attachment and proliferation of HGFs. SLA and GO treatment of implant surfaces results in significant improvement of osseointegration in vivo. Physicochemical modification of the titanium surface by SLA treatment and GO coating stimulates osteogenic activities of mesenchymal stem cells and improves biocompatibility to connective tissue cells, leading to enhancement of bone healing at the bone‐implant interface. Abstract : Physicochemical modifications of grade‐IV commercially pure titanium surface, which is used as a material of choice in clinical implant dentistry, by sandblasting, acid‐etching treatment and graphene oxide coating stimulate osteogenic activities of mesenchymal stem cells and improve biocompatibility to connective tissue cells. Graphene oxide enhances bone healing and osseointegration at bone‐implant interface.